Dual-Functional Fe3O4@SiO2/Ag/AgCl Nanocomposites as Photocatalyst for Degrading Methylene Blue Dye Under Natural Light Irradiation - Nguyen, Kha Minh; Pham, Nga Ngan; Tran, Hien Thi-Thu; Nguyen, Son Truong (Indonesian Journal of Chemistry, 2025)
The textile dyeing industry not only plays a crucial economic role in many nations but also significantly contributes to environmental pollution, particularly in aquatic environments. To mitigate this impact, various materials have been explored for their ability to remove dyes from wastewater. Among these, visible-light-responsive photocatalysts based on Ag nanomaterials have attracted considerable attention. However, challenges remain, including the degradation efficiency and the recoverability of photocatalysts. In this study, Fe3O4@SiO2/Ag/AgCl (FSAC) nanocomposites were synthesized and evaluated for methylene blue (MB) dye degradation under natural light irradiation. The magnetic properties of FSAC remained those of the core Fe3O4 nanoparticles, with a band gap energy of approximately 1.8 eV. Results showed that the photocatalytic decomposition of MB under 25 W natural light was significantly enhanced in the presence of the FSAC nanocomposites, compared to Fe3O4, Fe3O4@SiO2, and Fe3O4@SiO2/Ag nanoparticles. With its dual-functional magnetic and plasmonic properties, enabling both efficient recovery and superior catalytic performance, the FSAC composite holds excellent promise as a photocatalyst for the degradation of organic pollutants in water.